A magyar tőkebefektetések szerepe Kárpátalja gazdaságában - Imre, Gabriella (Közép-Európai Közlemények, 2012)
While Transcarpathia has never been the main destination for Hungarian outward FDI, in 2009 Hungary became the fourth largest investor in the economy of the Ukrainian border county accounted for a share of 10 per cent of total capital investments. The real interest of the Hungarian investments in Transcarpathia lies not in the amount of the invested capital but in the number and the size of the investing companies. According to the data of the Hungarian Investment and Trade Development Agency, in 2009 the number of companies with Hungarian participation in Transcarpathia increased to over 250 which can presume the high proportion of the Hungarian-owned SMEs among the investors. In our research the motivations and experiences of the Hungarian companies investing in Transcarpathia were analysed. In the first part of the paper, the IDP paradigm explaining the outward foreign direct investments of less developed countries is presented. In the following sections we briefly resume the research results concerning the FDI outflows of Central and Eastern European countries and especially concerning the Hungarian investments abroad. Finally, after dealing with the general characteristics of the Hungarian FDI in Transcarpathia we present the results of our survey. Our objective is to describe the region specific features of the Hungarian investments in Transcarpathia while the similarities with the FDI outflows of other new EU member states can also be detected.